Cognitive Limitation and Investment Performance: Evidence from Limit Order Clustering - Kuo, Wei-Yu; Lin, Tse-Chun; Zhao, Jing (Review of Financial Studies, 2015)
We hypothesize that cognitive limitation may be manifested in a disproportionately large volume of limit orders submitted at round-number prices if investors use these numbers as cognitive shortcuts. Using detailed limit order data in the Taiwan Futures Exchange, we find that investors with lower cognitive abilities, defined as higher limit order submission ratios at round numbers, suffer greater losses in their round-numbered and non-round-numbered limit orders, market orders, and round-trip trades. The positive correlation between cognitive ability and investment performance is monotonic and robust across futures and options markets. In addition, past trading experience helps mitigate cognitive limitation.